Wage Penalty of Abstinence and Wage Premium of Drinking - A misclassification bias due to pooling of drinking groups? - Johan Jarl; Ulf-G. Gerdtham (Lund University, School of Economics and Management, Department of Economics, 2009)
Several studies have found protective effects of low/moderate (hereafter "light") alcohol consumption compared with "abstinence" on mortality, health and wage. Some of these studies have been criticised because former drinkers have been included among the abstainers, which may overstate the protective effect of light alcohol consumption. It has also been proposed, but not shown, that the commonly pooled group of light drinkers and former heavy drinkers would understate the protective effect of light drinking. We also suggest that former abstainers might cause the same effect when pooled with light drinkers. The aim of this paper is to study whether pooled groups risk create bias in the form of misclassification and confounding. The analysis focuses on: 'former drinker error' (pooling of lifelong abstainers and former drinkers); 'former abstainer error' (pooling of former abstainers and lifelong light drinkers); and 'former heavy drinker error' (pooling of light drinkers with and without a history of heavy drinking). Swedish panel data were used in a multinomial logit model, presenting odds ratios when comparing the subgroups. The results demonstrate that commonly pooled groups are heterogeneous with respect to a number of variables, which may implicate confounding. Given appropriate controls, misclassification bias is likely in the pooled group of light drinkers. The direction of the misclassification bias, however, is to underestimate the beneficial effect of light alcohol consumption on wage and can therefore not explain the wage penalty of abstinence compared to light drinking.
Keywords: C10; I12; J31; 330; Alcohol consumption; Drinking history; Consumption groups; Misclassification bias